EDS1-mediated basal defense and SA-signaling contribute to post-invasion resistance against tobacco powdery mildew in Arabidopsis. (July 2015) - Zhang, Ling-Li; Ma, Xian-Feng; Zhou, Bin-Bin; Zhao, Ji-Qun; Fan, Jing; Huang, Fu; Li, Yan; Wang, Wen-Ming
Abstract: Arabidopsis-powdery mildew is a unique pathosystem in dissecting the molecular mechanism of plant-biotrophic fungus interactions. To increase the diversity of powdery mildew pathogens, we identified a tobacco powdery mildew, designated Gc SICAU1, which belonged to Golovinomyces cichoracearum ( Gc ) based on the internal transcribed spacer (ITS) rDNA fragment sequences. Inoculation test in laboratory conditions revealed that Gc SICAU1 could colonize on wild type Arabidopsis Col-0 leaves, but failed to grow as abundantly on tobacco leaves, indicating that Gc SICAU1 has completely overcome the pre-invasion resistance and its colonization is hindered by the post-invasion resistance in Arabidopsis . The growth of Gc SICAU1 in the fls2, efr-1 and pen1-1 mutants displayed no obvious difference from that of wild type plants. In contrast, salicylic acid (SA)-signaling deficient mutants such as pad4-1 and eds5-1, but not ethylene-signaling mutants, exhibited increased susceptibility to Gc SICAU1. Moreover, eds1-2 and pad4-1/sid2-1 were fully susceptible to Gc SICAU1 and the disease symptom was comparable to Gc SICAU1 on tobacco leaves. These data indicate that EDS1-mediated basal defense and SA-signaling play critical roles for post-invasion resistance against this pathogen. Taken together, our data demonstrated that Gc SICAU1 is a pathogen weakly virulent to Arabidopsis and can be used as a tool to finely dissect post-invasion resistance mechanisms. Highlights: A tobacco powdery mildew was identified as Golovinomyces cichoracearum SICAU1. Gc SICAU1 was a poorly-to-well adapted pathogen of Arabidopsis . Post-invasion defense hinders the growth of Gc SICAU1 on Arabidopsis . EDS1- and SA-signaling constitute the post-invasion defense against Gc SICAU1.